Identifying key nodes in complex networks based on an improved gravity model - Zhong, Linfeng; Gao, Xiangying; Zhao, Liang; Zhang, Lei; Chen, Pengfei; Yang, Hao; Huang, Jin; Pan, Weijun (Frontiers in Physics, 2023)
The identification of key nodes in complex networks is a hot topic. Therefore, it attracts increasing attention from different fields, like airline networks and social networks. To identify the key nodes in complex network, we suggest an improved gravity model method that takes propagation features into account. Relevant experiments were carried out in four actual airline networks based on the Susceptible Infected Recovered (SIR) model. Besides, Kendall's correlation coefficient and the imprecision function were used as evaluation metrics to analyze and validate the proposed method. Empirical results reveal that the suggested method outperforms previous benchmark methods in terms of precision and effectiveness for identifying key nodes, especially in the US air network, where Kendall's tau achieves a 107% improvement compared to the gravity centrality method.